Conflict, social capital, and managing natural resources [ a West African case study - Moore, Keith M. (CABI, 2005)
This book is the product of a six-year multi-disciplinary collaborative research program in sustainable agriculture and natural resource management. It describes the transition of the conflict-ridden agricultural and pastoral systems of arid and semi-ard regions of West Africa to more intensified agricultural and animal husbandry systems. The research investigates technological options and decision tools and explores a replicable methodology for building social capital within a rural community in the Inland Delta of the Niger River. The chapters recount the efforts of researchers and development agents to identify new approaches for sustainable development and the experiences of the local population seeking a pathway from poverty and food insecurity to a healthy economy and environment.